2000
DOI: 10.1056/nejm200009073431002
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Testosterone Treatment in Women with Impaired Sexual Function after Oophorectomy

Abstract: In women who have undergone oophorectomy and hysterectomy, transdermal testosterone improves sexual function and psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
404
3
19

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 874 publications
(444 citation statements)
references
References 25 publications
15
404
3
19
Order By: Relevance
“…Many of these studies were performed in women who received concomitant estrogen therapy. [107][108][109][110][111] Safety data are limited; long-term effects of testosterone, including effects on the breast, are unknown. Thus, applicability of testosterone is limited in women who have a history of breast cancer and in women who are unable to receive estrogen therapy.…”
Section: Low Libido and Sexual Dysfunctionmentioning
confidence: 99%
“…Many of these studies were performed in women who received concomitant estrogen therapy. [107][108][109][110][111] Safety data are limited; long-term effects of testosterone, including effects on the breast, are unknown. Thus, applicability of testosterone is limited in women who have a history of breast cancer and in women who are unable to receive estrogen therapy.…”
Section: Low Libido and Sexual Dysfunctionmentioning
confidence: 99%
“…36 The fact that this was not a placebocontrolled study is a limitation. However, this study tried to avoid any possibility of affecting how participants answered the questionnaire by not discussing sexual issues throughout the treatment period, and by emphasizing weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies addition of testosterone to estrogen therapy has been reported to improve sexual function and well-being. 120,121 In addition, beneficial effects on bone mineral density have been observed. 122 Despite the large number of studies investigating the effects of testosterone coadministration, there are limited long-term data regarding the cardiovascular safety of this combination therapy.…”
Section: Postmenopausal Testosterone Therapymentioning
confidence: 99%